Integration of CERC Model with Local Values ​​in Risk Communication in Indonesia - Jamil, Fathiyah (KOMUNIDA : Media Komunikasi dan Dakwah, 2025)
This article examines the integration of technology and local wisdom in disaster risk communication, focusing on the effectiveness of the CERC (Crisis and Emergency Risk Communication) model in Indonesia. It also examines how combining these elements can strengthen community resilience and improve disaster preparedness. This study uses a comprehensive literature review approach, analyzing various risk communication strategies and practices implemented in disaster-prone areas in Indonesia, based on relevant articles and studies. The analysis results show that combining modern technology, such as mobile applications and digital platforms, with local values ​​such as cooperation and solidarity, can improve public understanding and strengthen community participation in disaster risk management. This integration has also proven effective in improving community preparedness for disasters. This study recommends that disaster risk communication policies in Indonesia should utilize the potential of technology and local cultural values ​​to strengthen community resilience and reduce the impact of disasters. . Keywords: Technology Integration; local values; Community Resilience; Crisis and Emergency Risk Communication; Disaster Risk Communication